Bibliometric Analysis of Governance Research in Indonesia - Tamara, Masita Cindy; Poetri, Ashila Aulia; Rachmawati, Tutik; Parulian Simanjuntak, Jeremia Gom Gom; Vinazah, Ulivia; Aurelia, Marsya (KnE Social Sciences, 2022)
All research should make a significant contribution to the academic literature. However, this can only be achieved when research can highlight its novelty. Hence, mapping previous studies on a particular topic is essential to identify the uniqueness of the research. This study aimed to examine the growth of publications on governance issues in Indonesia using the Google Scholar database and manual searches in SINTA. This was a bibliometric analysis that relied on the Publish or Perish, Mendeley and VOSviewer tools. Studies from 352 journals were collected and analyzed to determine the development of publications on governance topics in Indonesia. Furthermore, using VOSviewer, co-authorship was analyzed and co-occurrence maps were created. The co-occurrence maps showed that the topics of corruption, public service and local governance were over-researched. On the contrary, the topics of district governance, good governance value, elite capture, and humanistic approach were under-researched. Hence, it is recommended that further research is conducted on these under-researched topics. Keywords: Indonesia governance, governance, bibliometric analysis